Extraction of Crude Sunflower Seed Oil as a Vegetable Oil Rich in Antioxidant using the Microwave Assisted Extraction (MAE) Method - Broto, Wisnu; Subagyo, Meylinda Dita Anggi (Diponegoro University, 2024)
Oil is a basic necessity in every county, palm oil is an oil that is in high demand so the palm oil industry has an impact on world deforestation. One raw material that can be substituted is sunflower seeds, with a high antioxidant content obtained from vitamin E and selenium, amount 41.08 mg/100 gr. So we eill get a sunflower seeds oil product that is rich in antioxidants, which is beneficial for health. Extraction of sunflower seed oil was carried out using the Microwave Assisted Extraction (MAE) extraction method with N-Hexane solvent. This study will use the factorial design level 23 method to determine the most influential process variables to produce optimum operating conditions in making sunflower seed oil with Quicker Method analysis where the changing process. The variables extraction are temperature (T), time (W), and solvent volume (V), and the most influential process variables were obtained, amount extraction time of 9 minutes, temperature of 60°C, and solvent volume of 500 mL producing an oil yield of 53.6%, viscosity of 53.76 cSt, density of 0.919 g/cm3, water content of 0.23% b /b, FFA of 0.32% w/w, and IC50 value of 87.613 is classified as a strong antioxidant.